If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 1 = 7 + -1m Reorder the terms: 1 + 3m = 7 + -1m Solving 1 + 3m = 7 + -1m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add 'm' to each side of the equation. 1 + 3m + m = 7 + -1m + m Combine like terms: 3m + m = 4m 1 + 4m = 7 + -1m + m Combine like terms: -1m + m = 0 1 + 4m = 7 + 0 1 + 4m = 7 Add '-1' to each side of the equation. 1 + -1 + 4m = 7 + -1 Combine like terms: 1 + -1 = 0 0 + 4m = 7 + -1 4m = 7 + -1 Combine like terms: 7 + -1 = 6 4m = 6 Divide each side by '4'. m = 1.5 Simplifying m = 1.5
| 7n-16=5n-2(-8-3n) | | 0+y=2 | | -4+2(4x+4)=3+8x | | 120=.5b*15 | | x/5=-1-(-7) | | -3-3(x-3)=3x+3(3-x) | | -(1-8n)+2=1+8n | | -4+x/9=-3 | | 200=45y+45+12y-16 | | 3+2(2x-5)-10x=8+4x | | -6(x+1)-10=12+2 | | 20x^3+17x^2+3x=0 | | 15+x=3x-1 | | 8+38=86 | | -5x-10=2-1(x+4) | | 6a-2+6a=-11+1+6a+7a | | 8+38=38 | | 33x^2-108x-96=0 | | x/25=-34+29 | | 8+28=-20 | | -1.5v-3=1.3333333v-.25 | | 74-8z=2 | | -12=6x+27x+2 | | 4x+5y=23 | | -18=-1.2y | | -6x=-108 | | 22*40*x=2500 | | 12X-83=5X-6 | | 0=3x^2-10x+8 | | 66x=2500 | | 2*(x-1)=3(-x-20-2x)-6x | | 5(-2+4)+2(n+3)= |